Peran Self Care Management Terhadap Lansia Osteoarthritis dalam Meningkatkan Quality of Life pada Lansia - Santi Fatmala; Vivin Nur Hafifah (FORIKES, 2021)
The aging process is a condition that is prone to health problems such as the incidence of osteoarthritis in the elderly. Osteoarthritis (OA) is a non-inflammatory degenerative joint disease that can affect the health of the elderly and tends to cause joint pain. The purpose of this systematic review is to determine the self-care management of the elderly with osteoarthritis. Database searches included Google Scholar, Cambridge, PubMed, and Proquest with the keywords self-care management in elderly osteoarthritis. The criteria for the selected articles were within 2017-2021, full text and in English or Indonesian. This systematic review used 15 articles that met the inclusion criteria. Physical exercise, education and family support are very influential management in the elderly with a history of osteoarthritis. Physical exercise, education and family support are non-pharmacological therapies that can improve their physical and psychological health in the elderly with osteoarthritis. Keywords: osteoarthritis; elderly; self care management; quality of life ABSTRAK Proses menua merupakan suatu kondisi yang rentan terhadap masalah-masalah kesehatan seperti kejadian osteoarthritis pada lansia. Osteoartritis (OA) merupakan penyakit sendi degeneratif non peradangan yang dapat mempengaruhi kesehatan lansia dan cenderung menibulkan nyeri sendi. Tujuan dari systematic review ini adalah untuk mengetahui manajemen perawatan diri lansia yang mengalami osteoarthritis. Pencarian database meliputi Google Scholar, Cambridge, PubMed, dan Proquest dengan kata kunci self-care management in elderly osteoarthritis. Kriteria artikel yang dipilih adalah dalam waktu 2017-2021, teks penuh dan berbahasa Inggris atau Indonesia. Systematic review ini menggunakan 15 artikel yang sesuai dengan kriteria inklusi. Latihan fisik, edukasi serta dukungan keluarga merupakan manajemen yang sangat berpengaruh pada lansia dengan riwayat osteoarthritis. Latihan fisik, edukasi serta dukungan keluarga merupakan terapi non farmkologis yang dapat meningkatkan kesehatannya secara fisik maupun psikologi pada lansia dengan osteoarthtritis. Kata kunci: osteoarthritis; lansia; self care management; quality of life